Pareti verticali e LiDAR: esperienze dalle Dolomiti (GEOmedia, 2010)
Dolomites in 3D thanks to laser scannerPeak3D is the project created to return in three dimensions the verticality of the mountains. In this project 8 companies and institutions are involved : The University of Pavia, The Foundation Bruno Kessler, The University of Padua, The University of Milan Bicocca, Codevintec, Helica, Gexcel and Protocube. Peak3D has dedicated itself to the Dolomites detected by the laser scanner. The data obtained allow many uses.